Development of the red gum lerp psyllid Glycaspis brimblecombei (Hemiptera: Aphalaridae) in Eucalyptus spp. - Pereira, Jaqueline Magalhães; Baldin, Edson Luiz Lopes [UNESP]; Soliman, Everton Pires; Wilcken, Carlos Frederico [UNESP] (Instituto de Pesquisa e Estudos Florestais (IPEF), 2021)
The red gum lerp psyllid, Glycaspis brimblecombei Moore (Hemiptera: Aphalaridae), is considered one of the most important pests of Eucalyptus worldwide. Since its detection in Brazil in 2003, the insect has caused defoliation in forests, twig dieback and sooty mold. Several types of management were evaluated, but few studies focused on the search for resistant Eucalyptus species and hybrid clones. The present study aimed to assess the biological performance of G. brimblecombei on E. camaldulensis, E. urophylla, and E. grandis and on the hybrids E. grandis x E. camaldulensis (1277 and 3025), E. urophylla x E. camaldulensis (VM-01), and E. urophylla x E. grandis (C-219, H-13, GG-100 and I-144), in order to determine resistance mechanisms. Under laboratory conditions (T= 26 ± 2°C; RH= 60 ± 10%; photoperiod= 12 h), psyllids on each of the ten Eucalyptus genotypes were evaluated daily until adult emergence. Genotypes C-219 and H-13 (E. urophylla x E. grandis) exhibited high levels of antibiosis and/or antixenosis (non-preference) resistance to G. brimblecombei, drastically reducing nymph viability (mortality > 80%). In turn, genotypes 3025 (E. grandis x E. camaldulensis) and E. camaldulensis were highly susceptible to the biological development of red gum lerp psyllids. Our results may contribute to genetic improvement programs aimed at obtain G. brimblecombei resistant Eucalyptus genotypes.
Desenvolvimento do psilídeo-de-concha Glycaspis brimblecombei (Hemiptera: Aphalaridae) em Eucalyptus spp.
Keywords: Antibiosis; Antixenosis; Forest pest; Host plant resistance